Functional physiological, psychological, and biochemical reactivity to socially evaluated cold pressor test in hereditary angioedema patients (FRoSEn) - De Maria, Beatrice; Ranucci, Luca; Gino, Clara; Cesoni Marcelli, Azzurra; Zingale, Lorenza Chiara; Zulueta, Aida; Dalla Vecchia, Laura Adelaide; Gorini, Alessandra; Perego, Francesca (Frontiers in Immunology, 2026)
IntroductionStressful physical or psychological events can trigger acute swelling attacks in patients with Hereditary Angioedema due to C1 Inhibitor deficiency (HAE-C1INH), although the stress–disease relationship remains unclear. The Socially Evaluated Cold Pressor Test (SECPT) reliably induces acute stress under controlled conditions. This study aimed to compare perceived stress, inflammatory markers, and cardiovascular responses to SECPT between HAE-C1INH patients and healthy controls (HC).MethodsTwenty HAE-C1INH patients (9 males, 44 ± 14 years) and age and sex matched HC underwent a 3-minute SECPT. Participants completed questionnaires assessing anxiety and depression (HADS), pain catastrophizing (PCS), and subjective stress (0–100 scale) before and after SECPT. Heart rate (HR) and arterial pressure (AP) were recorded. Blood samples for inflammatory cytokines (IL-6, IL-1ß, TNF-α) were collected at baseline, and 10 and 40 minutes after SECPT.ResultsCompared to HC, patients showed higher baseline HADS-A (7.3 ± 4.5 vs 4.7 ± 2.7), overall PCS (19.7 ± 12.6 vs 12.9 ± 8.7), and perceived stress during SECPT (60.6 ± 34.3 vs 34.6 ± 23.8). IL-6 levels were higher at baseline and 10 minutes post-test (2.63 ± 1.21 vs 1.84 ± 0.87; 2.78 ± 1.20 vs 1.91 ± 0.79 pg/ml), as were TNF-α levels across all phases (4.19 ± 1.38 vs 3.26 ± 1.55; 4.09 ± 1.39 vs 3.40 ± 1.48; 4.09 ± 1.28 vs 3.20 ± 1.57) while IL-1 ß remained unchanged. HR and AP variations were similar between groups.DiscussionHAE-C1INH patients exhibited heightened perceived stress response to SECPT, and elevated baseline inflammation, despite comparable cardiovascular reactivity. These findings highlight a complex psychophysiological–inflammatory interplay in acute stress responses, suggesting the need to integrate psychological and biological frameworks in understanding HAE-C1INH triggers.Clinical trials codeNCT06414252.